PERAN HARGA DAN PENDAPATAN DALAM MEMODERASI PENGARUH GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN IPHONE PADA KONSUMEN GENERASI Z - Safirah, Holifatuz; Purwanto, Edy (Journal MISSY (Management and Business Strategy), 2024)
In this modern era, technological developments are very rapid, starting from household appliances to communication tools, thus providing convenience for someone to communicate directly and carry out activities at home. As with the advent of smartphones, someone can work from home or perform other activities, because smartphones have smart applications that make users easier to carry out activities anywhere and anytime using smartphones, even able to make money. The object of this research is the iPhone. The purpose of this study is to examine the role of price and income in moderating the influence of lifestyle on purchasing decisions of iPhones among Generation Z consumers. The sampling technique in this study uses purposive sampling. The analysis techniques used are validity tests, reliability tests, classic assumption tests, simple linear regression tests, and MRA (Moderated Regression Analysis). The results of the study show that lifestyle (X) significantly influences purchasing decisions (Y), where the price moderation variable (M1) indicates that price can moderate the relationship between lifestyle variables and purchasing decision variables so that it can be said to be a pure moderator, and the income moderation variable (M2) indicates that income can moderate the relationship between lifestyle variables and dependent variables so that it can be said to be pure moderators.